Selective on-surface covalent coupling based on metal-organic coordination template - Xing, Shuaipeng (Nat Commun, 2019)
Control over on-surface reaction pathways is crucial but challenging for the precise construction of conjugated nanostructures at the atomic level. Herein we demonstrate a selective on-surface covalent coupling reaction that is templated by metal-organic coordinative bonding, and achieve a porous nitrogen-doped carbon nanoribbon structure. In contrast to the inhomogeneous polymorphic structures resulting from the debrominated aryl-aryl coupling reaction on Au(111), the incorporation of an Fe-terpyridine (tpy) coordination motif into the on-surface reaction controls the molecular conformation, guides the reaction pathway, and finally yields pure organic sexipyridine-p-phenylene nanoribbons. Emergent molecular conformers and reaction products in the reaction pathways are revealed by scanning tunneling microscopy, density functional theory calculations and X-ray photoelectron spectroscopy, demonstrating the template effect of Fe-tpy coordination on the on-surface covalent coupling. Our approach opens an avenue for the rational design and synthesis of functional conjugated nanomaterials with atomic precision.